Tweed and black and white art - Gaitán, Carmen; Gaitán, Candela (I+Diseño. Revista Científica de Investigación y Desarrollo en Diseño, 2011)
It has often been said that black is the most elegant colour for attending any social or artistic event; however, white competed against it and sometimes won the battle. It was precisely Coco Chanel, one of the great couturiers of the 20th century, who characterised the first decades of the 20th century with both shades, namely black in the 1920s and white in the 1930s. Now, it is the reinvented tweed suit of 1954, revived from the model she made in 1925, which combines these opposite colours.